"I lied a little bit." A qualitative study exploring the perspectives of elite Australian athletes on self-reported data - Coventry, M.; Timler, A.; Mosler, A. B.; Russell, K.; Travers, M.; Oam, L. M.; Murphy, M. C. (Physical Therapy in Sport, 2023)
Objectives Explore the perceptions and experiences of elite Australian athletes` engagement with reporting data in surveillance systems.